Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41569-018-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary metabolism, the gut microbiome, and heart failure

Abstract: The contribution of gut microbiota to human health and diseases has expanded our insights into how microbial composition and function impacts the human host. Heart failure has long been associated with splanchnic circulation congestion, leading to bowel wall edema and impaired intestinal barrier function. This is thought to heighten the overall inflammatory state via enhanced bacterial translocation and the presence of bacterial products in the systemic circulation. Recently, several metabolites produced by gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
401
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(466 citation statements)
references
References 232 publications
(278 reference statements)
8
401
1
9
Order By: Relevance
“…The identification of TMAO as a CVD‐relevant biomarker is a notable example of a disease‐relevant microbial metabolite discovery. By using an untargeted metabolomic approach, Hazen et al identified dozens of metabolites, including choline, TMA, and TMAO – which were significantly different in the cases of CVD compared with age‐ and gender‐matched controls – and confirmed their observations by using several validation cohorts . They then proved that the identified metabolites are from a gut microbiota‐dependent pathway by using traceable isotope‐labeled compounds in animal studies and by establishing the causal role of TMAO in atherogenesis and thrombosis in animal and cell models.…”
Section: Discovery Of Gut Microbiota‐specific Bioactive Metabolitesmentioning
confidence: 89%
See 1 more Smart Citation
“…The identification of TMAO as a CVD‐relevant biomarker is a notable example of a disease‐relevant microbial metabolite discovery. By using an untargeted metabolomic approach, Hazen et al identified dozens of metabolites, including choline, TMA, and TMAO – which were significantly different in the cases of CVD compared with age‐ and gender‐matched controls – and confirmed their observations by using several validation cohorts . They then proved that the identified metabolites are from a gut microbiota‐dependent pathway by using traceable isotope‐labeled compounds in animal studies and by establishing the causal role of TMAO in atherogenesis and thrombosis in animal and cell models.…”
Section: Discovery Of Gut Microbiota‐specific Bioactive Metabolitesmentioning
confidence: 89%
“…40 Both indoxyl sulfate and FIGURE 1 Crosstalk between gut microbial metabolites and organs beyond the gut through the gut-systemic axis ↑foam cell formation, ↓reverse cholesterol transport, ↑platelet aggregation potential. Target receptor remains unknown 33,34 Indoxyl sulfate Tryptophan Uremic toxin proposed to aggravate chronic renal disease, CVD, as well as CKD related bone disorders 21,35 Enter proximal renal tubular cell through organic anion transporter and cause oxidative stress by activating ROS system 21,35 p-Cresol sulfate Tyrosine, phenylalanine…”
Section: Microbial Metabolites Are Messengers In the Gut-systemic Amentioning
confidence: 99%
“…Several relatively small studies in patients have attempted to characterize HF gut microbiota profile, even if inconsistencies and discrepancies have also been outlined [82]. Since gut microbial transplantation has been already proven to provide diseases Alterations in gut permeability, changes in diversity and composition of gut microbiome and elevated circulating levels of LPS have been already identified in patients with HF, triggering a state of chronic inflammation [84,87,88]. Several relatively small studies in patients have attempted to characterize HF gut microbiota profile, even if inconsistencies and discrepancies have also been outlined [82].…”
Section: Role Of Gut Microbiota In Hfmentioning
confidence: 99%
“…Host microbes have been shown to bolster or suppress the effects of fluoropyrimidines, a treatment for colorectal cancer with highly variable efficacy . Moreover, the gut microbiome secretes bioactive metabolites, like short‐chain fatty acids, amino acid metabolites, and secondary bile acids, which may modulate disease progression . Changes in the microbiome secondary to tuberculosis treatment may impact the course of disease .…”
Section: Experience With Pk‐pd Modeling and Research Areas Going Forwardmentioning
confidence: 99%
“…48 Moreover, the gut microbiome secretes bioactive metabolites, like short-chain fatty acids, amino acid metabolites, and secondary bile acids, which may modulate disease progression. 49 Changes in the microbiome secondary to tuberculosis treatment may impact the course of disease. 50 These studies point to the possibility of developmental changes in the microbiome affecting the variability of PD.…”
Section: Experience With Pk-pd Modeling and Research Areas Going Forwardmentioning
confidence: 99%